Anisotropic oxide ion conduction in melilite intermediate temperature electrolytes. Issue 6 (7th January 2015) - Wei, Fengxia; Gasparyan, Hripsime; Keenan, Philip J.; Gutmann, Matthias; Fang, Yanan; Baikie, Tom; Claridge, John B.; Slater, Peter R.; Kloc, Christian L.; White, Tim J.
Abstract : Melilite, a tetrahedral-layered structure, shows strong anisotropic oxygen ion conduction at intermediate temperatures, which can be controlled by increasing the number of interstitial oxygen and reducing the size of interlayer cations. Abstract : Electrolytes with oxide ion conductivities higher than 10 −2 S cm −1 at moderate temperatures (∼500–900 °C) offer the possibility for solid oxide fuel cells to operate with less maintenance. This study of [A1+ x B1− x ]2 [Ga]2 [Ga2 O7+ x /2 ]2 (0 ≤ x ≤ 0.5) (A = La, Nd; B = Ca, Sr) layered-melilite found that in large single crystals intralayer oxide ion conduction is dominant. This anisotropic behavior arises by relaxation about the interstitial oxygen through changes in the interlayer A and Ga coordination, and at 850 °C conductivities are ∼0.008 S cm −1 along the c direction and ∼0.036 S cm −1 perpendicular to the c axis. It is found that the ionic conductivity can be optimized by increasing the number of interstitial oxygen and reducing the size of interlayer cations.